Tranen van bloed Het beleg van 's-Hertogenbosch en de oorlog in de Nederlanden, 1629 - de Cauwer, Peter (Amsterdamse Gouden Eeuw Reeks, 2008)
The Siege of 's-Hertogenbosch and the Campaign of 1629 is one of the most illustrious events of the Eighty Years' War in the history of the Netherlands. However, its image and interpretations have hardly changed in the past decades, in particular its international significance, as well as the story of the losing side: the Dutch Spaniards and the city of 's-Hertogenbosch, which has so far remained underexposed. Based on broad and often unused source material, this book sheds a new light on this "glorious, but dangerous years" event. In addition to the political and military aspects, this book also provides insight into the experiences and opinions of ordinary soldiers, city- and rural dwellers. This approach creates new insights into the war in the Netherlands, where the Siege of 's-Hertogenbosch is indeed justly affirmed as an impressive event.